2010
DOI: 10.1177/1948550610372145
|View full text |Cite
|
Sign up to set email alerts
|

Political Ideology at Face Value

Abstract: Four studies demonstrated that perceivers were able to identify the political attitudes of unknown politicians on a left-right dimension when the targets were merely shown in photographs. In Study 1, party membership provided an objective criterion for political attitudes, whereas actual voting behavior served as a validity criterion in Studies 2, 3a, and 3b. All studies yielded ratings highly chance accuracy. Additional ratings suggest that perceived dominance may partly account for the effect. Moreover, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 38 publications
7
72
0
Order By: Relevance
“…Several other studies have recently presented evidence in support of a relationship between character and facial appearance in humans (e.g. Kramer, King, & Ward, 2011;Samochowiec, Wänke, & Fiedler, 2010;Stirrat & Perrett, 2010) and it is therefore possible that character-driven mate-choice copying can take place even when the character of the model is not explicitly known.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have recently presented evidence in support of a relationship between character and facial appearance in humans (e.g. Kramer, King, & Ward, 2011;Samochowiec, Wänke, & Fiedler, 2010;Stirrat & Perrett, 2010) and it is therefore possible that character-driven mate-choice copying can take place even when the character of the model is not explicitly known.…”
Section: Discussionmentioning
confidence: 99%
“…As argued in a number of these studies, this suggests that voters hold (partly correct) stereotypic associations between the ideology of politicians and their facial metrics and gestures (Carpinella & Johnson, 2013;Samochowiec et al, 2010). Detailed investigations of the content of these stereotypes have shown that a "dominant" look is associated with a right-wing rather than left-wing ideology (Samochowiec et al, 2010) and a "powerful" Downloaded by [Florida Atlantic University] at 23:49 10 August 2015 look is associated with being Republican and a "warm" and non-dominant look with being Democrat . 4 On this basis, we predict-in parallel to studies of explicit cues of ideology-that liberal audiences are more willing to follow non-dominant-looking sources and conservative audiences are more likely to follow dominant-looking sources.…”
Section: Nonverbal Source Cues and Partisan Stereotypesmentioning
confidence: 95%
“…Specifically, several studies have shown that naive subjects can predict the party affiliation and ideological leanings of U.S., British, German, and Swiss politicians by merely looking at photos of the politicians' faces (Bull & Hawkes, 1982;Jahoda, 1954;Samochowiec et al, 2010; however see also Olivola & Todorov, 2010b). As argued in a number of these studies, this suggests that voters hold (partly correct) stereotypic associations between the ideology of politicians and their facial metrics and gestures (Carpinella & Johnson, 2013;Samochowiec et al, 2010). Detailed investigations of the content of these stereotypes have shown that a "dominant" look is associated with a right-wing rather than left-wing ideology (Samochowiec et al, 2010) and a "powerful" Downloaded by [Florida Atlantic University] at 23:49 10 August 2015 look is associated with being Republican and a "warm" and non-dominant look with being Democrat .…”
Section: Nonverbal Source Cues and Partisan Stereotypesmentioning
confidence: 99%
“…As Hull (1928) put it, "The results as a whole certainly look very bad for the judgment of character on the basis of photographs" (p. 119). Yet, there has been a flurry of recent research claiming to demonstrate that people can accurately guess a variety of internal traits and behavioral tendencies from facial photographs, such as political orientation (Rule & Ambady 2010, Samochowiec et al 2010, but see Olivola & Todorov 2010b), sexual orientation (Rule & Ambady 2008b, Rule et al 2009b; but see Olivola & Todorov 2010b), and even criminal behavior , Valla et al 2011; but see Olivola & Todorov 2010b. However, the conclusion that a person's facial appearance is a valid indicator of his/her underlying characteristics suffers from numerous shortcomings that have not been properly addressed in many of these studies.…”
Section: Accuracy Of Social Attributions From Facesmentioning
confidence: 99%